2011
DOI: 10.1186/1476-069x-10-99
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mercury exposure on blood pressure, resting heart rate and heart rate variability in French Polynesians: a cross-sectional study

Abstract: BackgroundPopulations which diet is rich in seafood are highly exposed to contaminants such as mercury, which could affect cardiovascular risk factorsObjectiveTo assess the associations between mercury and blood pressure (BP), resting heart rate (HR) and HR variability (HRV) among French PolynesiansMethodsData were collected among 180 adults (≥ 18 years) and 101 teenagers (12-17 years). HRV was measured using a two-hour ambulatory electrocardiogram (Holter) and BP was measured using a standardized protocol. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
(51 reference statements)
1
31
1
2
Order By: Relevance
“…In addition, although some prior research has shown an association between Hg and baseline HRV (4850), we found no such associations in our data. However, significant interactions between Hg and vagal responses to acute stress were found in predicting ASQ.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, although some prior research has shown an association between Hg and baseline HRV (4850), we found no such associations in our data. However, significant interactions between Hg and vagal responses to acute stress were found in predicting ASQ.…”
Section: Discussioncontrasting
confidence: 99%
“…The cardiovascular risk of methylmercury exposure has also been more extensively explored in adults than in children. Methylmercury exposure has a known effect on the autonomic nervous system, and in particular on heart rate variability (Lim et al 2010; Valera et al 2008; Valera et al 2011; Valera et al 2012; Yaginuma-Sakurai et al 2010). Mercury exposure has also been associated with an increased risk of myocardial infarction and accelerated progression of carotid atherosclerosis (Choi et al 2009; Salonen et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…PP has been found to be an independent predictor of future cardiovascular risk (Safar et al, 2003). PP is widely used in the literature, including several recent studies on whole blood total mercury (Valera et al, 2011a; Valera et al, 2011b) toenail mercury (Mordukhovich et al, 2012), or hair mercury (Valera et al, 2011a; Virtanen et al, 2012b); however, only one reported an association of PP with mercury, and this was only observed in unadjusted analyses (Valera et al, 2011a). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies report no association of SBP or DBP with THg in blood among women (Nielsen et al, 2012), in both sexes (Bautista et al, 2009; Valera et al, 2011b), or among fish consumers (Vupputuri et al, 2005); with THg in hair (Bautista et al, 2009; Virtanen et al, 2012b); or with toenail mercury (Mordukhovich et al, 2012). While Valera et al observed a crude association of blood mercury with both SBP and DBP in a population of Canadian Cree, this did not persist after adjustment for confounders, including serum n-3 PUFAs and selenium (Valera et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%